2022
DOI: 10.3390/ani12192569
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the Viscum Species for Diet and Medicinal Purposes in Ruminants: A Review

Abstract: A cost-effective, alternative protein and mineral source such as the Viscum species can be key to livestock production. Viscum spp. are used as feed in many semi-arid and arid regions globally, particularly during feed shortages. The species’ feeding value, and their pharmaceutical attributes, have been recognized worldwide, albeit with variation in nutritive value from one host to another. The antinutritional factors found in Viscum spp. may benefit livestock when consumed in moderation due to their immunomod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Furthermore, veterinary medicine and/or homeopathy are the most promising fields for future applications [ 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 ], not excluding the antiviral properties, which ask for further continuous attention [ 262 ]. Therefore, the knowledge about European mistletoe properties is in continuous evolution and requires a continuous revision of its use in evidence-based complementary and alternative medicine [ 263 , 264 , 265 , 266 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, veterinary medicine and/or homeopathy are the most promising fields for future applications [ 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 ], not excluding the antiviral properties, which ask for further continuous attention [ 262 ]. Therefore, the knowledge about European mistletoe properties is in continuous evolution and requires a continuous revision of its use in evidence-based complementary and alternative medicine [ 263 , 264 , 265 , 266 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other mistletoe genus ( Viscum spp. ), flavonoids, alkaloids and saponins were identified ( Hawu et al, 2022 ). Compounds belonging to hydroxycinnamic acid derivatives like coumaric acid, ferulic acid, caffeic acid and chlorogenic acid are phytochemicals present in the fruits and aerial pars of several plants, which are known to exert beneficial effects linked to their antioxidant and anthelmintic activity ( Mancilla-Montelongo et al, 2019 ; Ondua et al, 2021 ; Orzuna-Orzuna et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The phenolic compound content of yellow mistletoe was lower than those reported by Hernández-Luna et al (2017), and higher than that reported for mistletoe. Viscum rotundifolium with 7.3 g/kg DM of total tannins (Hawu et al, 2022). In traditional Mexican medicine of black mistletoe, as it is a medicinal plant used for the treatment of several ailments like an anti-inflammatory and nervous system relaxant (Biblioteca Digital de la Medicina Tradicional Mexicana, 2022), and has also been shown to have antimicrobial activity against Clavibacter michiganenses (García-García et al, 2021).…”
Section: Discussionmentioning
confidence: 99%